Impact of early percutaneous dilatative tracheostomy in patients with subarachnoid hemorrhage on main cerebral, hemodynamic, and respiratory variables: A prospective observational study - Bini, Giovanni; Russo, Emanuele; Antonini, Marta Velia; Pirini, Erika; Brunelli, Valentina; Zumbo, Fabrizio; Pronti, Giorgia; Rasi, Alice; Agnoletti, Vanni (Frontiers in Neurology, 2023)
Introduction Patients with poor-grade subarachnoid hemorrhage (SAH) admitted to the intensive care unit (ICU) often require prolonged invasive mechanical ventilation due to prolonged time to obtain neurological recovery. Impairment of consciousness and airway protective mechanisms usually require tracheostomy during the ICU stay to facilitate weaning from sedation, promote neurological assessment, and reduce mechanical ventilation (MV) duration and associated complications. Percutaneous dilatational tracheostomy (PDT) is the technique of choice for performing a tracheostomy. However, it could be associated with particular risks in neurocritical care patients, potentially increasing the risk of secondary brain damage. Methods We conducted a single-center, prospective, observational study aimed to assess PDT-associated variations in main cerebral, hemodynamic, and respiratory variables, the occurrence of tracheostomy-related complications, and their relationship with outcomes in adult patients with SAH admitted to the ICU of a neurosurgery/neurocritical care hub center after aneurysm control through clipping or coiling and undergoing early PDT. Results We observed a temporary increase in ICP during early PDT; this increase was statistically significant in patients presenting with higher therapy intensity level (TIL) at the time of the procedural. The episodes of intracranial hypertension were brief, and appeared mainly due to the activation of cerebral autoregulatory mechanisms in patients with impaired compensatory mechanisms and compliance. Discussion The low number of observed complications might be related to our organizational strategy, all based on a dedicated “tracheo-team” implementing both PDT following a strictly defined protocol and accurate follow-up.